Ancient Indian sciences : technical and scientific literature and practices in ancient India - Kapoor, Subodh (Cosmo, 2003)
Vol.1.Ancient Indian mathematics. Arya sidhantha and parasara. Sulbas. Hindu geometry.Medicine.Ayurveda. Vol.2. Principles of ayurveda.Life sciences and bhagavathapurana. Hindu astronomy. Astrology.Vol.3.Vedic physics.Ancient Indian aircraft.Vastu sastra. science and vedanta.